Progressivity Of Criminal Handling Fraud And Disease By The Directorate Of The General Criminal Reserse Of Central Java Regional Police (POLDA) - Ni Made Srinitri; Umar Ma'ruf; Munsharif Abdul Chalim (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
This study aims to determine and analyze the process of handling fraud and embezzlement by Central Java Regional Police Criminal Investigation investigators and the progress of handling fraud and embezzlement crime at the Central Java Regional Police Criminal Investigation Directorate. The approach method used is empirical juridical with descriptive analytical research specifications. The data used in the form of primary data and secondary data so that the method of data collection through field studies and literature studies. Data analysis method used is qualitative analysis. As a knife of analysis, the concepts of restorative justice, legal system theory and progressive legal theory are used.The results of the study concluded that the process of investigating fraud and embezzlement in the East Java Regional Police Criminal Investigation Directorate was in accordance with the provisions of the Criminal Procedure Code and the National Police Chief Regulation Number 6 of 2019 on Criminal Investigations. The progress in handling fraud and embezzlement in the Central Java Regional Police Criminal Investigation Directorate is related to the application of restorative justice in investigating criminal acts that starts with two components of the legal basis, namely rules and behavior. The regulatory component appears from a number of legal rules regarding the application of restorative justice in investigations that have been regulated in police regulations,Keywords: Progressiveness; Fraud And Embezzlement; Restorative Justice.